FINANCIAL ACCOUNTING APPROACH FOR DECISION MAKING: A CASE ON FOOD RETAILER COMPANY - Putra, Yuniarti Hidayah Suyoso (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
This paper aims to evaluate food retailer company based on the financial accounting approach by analyzing statement of financial performance, statement of financial position, statement of cash flow, common size and key market indicators. The research focuses on Woolworths’ Company Limited over period of five years from 1999 to 2003 and compare with competitors Coles Myer Limited and Foodland Limited.  The results show Woolworths’ performance over the five years period is improving with gradual increase in net profit margin, return on assets, and the decrease in tax rate and interest expense. Whilst, In short term, working capital ratio and quick assets ratio has been decreased over the past five years which means its current assets is not able to cover up its current liabilities. However, in examining debtor’s turnover (in days), inventory turnover and operating cycle the company is able to sell out its inventories and collect debts quickly which may increase the company’s ability to raise funds when it is needed. Furthermore, in the long term financial stability, Woolworths is using a high level of debt which contributes two thirds of the company’s total assets. Meanwhile, shareholders’ funds only increased as half as it liabilities from 1999 to 2003. Therefore, based on all the analysis, Woolworths is predicted to remain in the food and drug retailing industry.